A saturated feedforward/cascade controller for passive continuous reacting systems using entropy production shaping. (September 2019) - Zárate-Navarro, Marco A.; García-Sandoval, J. Paulo; Hudon, Nicolas
Abstract: A control scheme is proposed for adiabatic continuous chemical reactors using thermodynamic properties. This control scheme is inspired by the general advantages of cascade control and Passivity-based Control, using the internal entropy production as a storage function, leading to a transparent physical interpretation. The inner loop shapes the entropy production function (the potential that generates the dynamics) to guarantee stability, while the outer loop regulates process variables such as temperature, pressure, or conversion. The resulting control scheme is equivalent to a feedforward/PI control with control saturations, subject to the available potential and the bounds of the manipulated variable. The controller parameters are given by the physical properties of the system and only a single proportional parameter needs to be tuned to regulate a process variable to its desired value.